PENDIDIDIKAN ISLAM ANTARA HARAPAN DAN REALITA - Nanda Khairiyah (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2019)
The Islamic education had a strategic of role in modern society life. It’s goal was to make the people (students) in order to be a good personality and a good character. The quintessence that the Islamic education at school have to develop of students’ cognitive, affective and psychomotoric aspects. By implementating of the government’s needed, society and stakeholders have to have a good political will. The ideal hope of the Islamic education (national) in order to the education output of strong and responsibility of young generation. The reality that there are still the education output are still not quality yet in order to have many education outcomes are still jobless. The Islamic education assignment must be educated with integrated and holistics and long life education processing. The Islamic education was to fulfill the students’ needs, both spiritual, intelectual, moral, aesthetics and physical needs based on the Islamic values. The function of Islamic education was to prepare the facilities who develop possible of the students as sistymatic, aimed and comprehensive. While, the Islamic education target was the students who grow and develop as dynamic, becoming from unborn child to end their life.